Design of CTP-PRO study (impact of stress Cardiac computed Tomography myocardial Perfusion on downstream resources and PROgnosis in patients with suspected or known coronary artery disease: A multicenter international study). (1st October 2019) - Pontone, Gianluca; De Cecco, Carlo; Baggiano, Andrea; Guaricci, Andrea I.; Guglielmo, Marco; Leiner, Tim; Lima, Joao; Maurovich-Horvat, Pál; Muscogiuri, Giuseppe; Nance, John W.; Schoepf, U. Joseph
Abstract: Background: CT myocardial perfusion imaging (CTP) represents one of the newly developed CT-based techniques but its cost-effectiveness in the clinical pathway is undefined. The aim of the study is to evaluate the usefulness of combined evaluation of coronary anatomy and myocardial perfusion in intermediate to high-risk patients for suspected CAD or with known disease in terms of clinical decision-making, resource utilization and outcomes in a broad variety of geographic areas and patient subgroups. Methods: CTP-PRO study is a cooperative, international, multicentre, prospective, open-label, randomized controlled study evaluating the cost-effectiveness of a CCTA+CTP strategy (Group A) versus usual care (Group B) in intermediate-high risk patients with suspected or known CAD who undergo clinically indicated diagnostic evaluation. A total sample size of 2000 subjects will be enrolled and followed up for 24 months. The primary endpoint is the reclassification rate of CCTA in group A due to the addition of CTP. The secondary endpoint will be the comparison between groups in terms of non-invasive and invasive downstream testing, prevalence of obstructive CAD at ICA, revascularization, cumulative ED and overall cost during the follow-up at 1- and 2-years. The tertiary endpoint will be the comparison between each group in terms of MACE and cost-effectiveness at 1- and 2-years. Conclusions: The study will provide information to patients, health care providers and other stakeholders about which strategy could be more effective in the diagnosis of suspected CAD in intermediate to high-risk patients or in the symptomatic patients with known CAD and previous history of revascularization. Highlights: CTP-PRO study is a prospective, randomized study evaluating the cost-effectiveness of a CCTA+CTP strategy (Group A) versus usual care (Group B). A total sample size of 2000 subjects will be enrolled and followed up for 24 months. Primary endpoint: reclassification rate of CCTA in group B due to the addition of CTP. Secondary endpoint: comparison of downstream testing, prevalence of obstructive CAD, revascularization, cumulative ED and overall cost. Tertiary endpoint: comparison between each group in terms of MACE and cost-effectiveness at 1- and 2-years.